1986
DOI: 10.1017/s0043174500067205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adjuvants and Application Variables on Postemergence Weed Control with Bentazon and Sethoxydim

Abstract: Experiments were conducted at Urbana, IL, in 1983 and 1984 to determine the effect of adjuvants, adjuvant rate, and carrier volume on postemergence weed control with bentazon [3-(1-methylethyl)-(1H)-2,1,3-benzothiadiazin-4(3H)-one 2,2-dioxide] and sethoxydim {2-[1-(ethoxyimino)butyl]-5-[2-(ethylthio)propyl]-3-hydroxy-2-cyclohexen-1-one} in soybeans [Glycine max(L.) Merr. ‘Williams’]. Little difference was observed between a petroleum oil:emulsifier blend (83:17, v/v) (POC) and a soybean oil: emulsifier blend (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Herein we report on the successful application of near‐ambient‐pressure X‐ray photoelectron spectroscopy (NAP‐XPS) to investigate the influence of the reactive gas phase on the surface potential barrier of VPP under catalytic n ‐butane oxidation conditions with proven production of maleic anhydride. The results show that the transfer of charge carriers between the bulk catalyst and the surface can be explained by—and are thus the first experimental proof for—the previously only theoretically proposed semiconductor catalyst concepts of Boudart,1 Schwab,2 Volkenshtein,3 and Morrison 4. 5 We compare these results with the electronic response of the unselective oxidation catalyst V 2 O 5 and the moderately selective catalyst MoVTeNbO x (orthorhombic M1 phase) in order to identify a general concept that can explain selectivity.…”
supporting
confidence: 59%
“…Herein we report on the successful application of near‐ambient‐pressure X‐ray photoelectron spectroscopy (NAP‐XPS) to investigate the influence of the reactive gas phase on the surface potential barrier of VPP under catalytic n ‐butane oxidation conditions with proven production of maleic anhydride. The results show that the transfer of charge carriers between the bulk catalyst and the surface can be explained by—and are thus the first experimental proof for—the previously only theoretically proposed semiconductor catalyst concepts of Boudart,1 Schwab,2 Volkenshtein,3 and Morrison 4. 5 We compare these results with the electronic response of the unselective oxidation catalyst V 2 O 5 and the moderately selective catalyst MoVTeNbO x (orthorhombic M1 phase) in order to identify a general concept that can explain selectivity.…”
supporting
confidence: 59%
“…Some of these reports show that the reduced control with higher volumes can be increased by increased adjuvant concentration, but Smeda and Putnam (22) found that there was no inter action between carrier volume and adjuvant concentra tion, suggesting that the effects of these two variables are independent of one another. Other researchers have reported comparatively little effect of spray volume on the phytotoxicity obtained with graminicides, or they have found that higher spray volumes enhance control when treated plants are under drought stress (13,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…Weed control with POST herbicides is influenced by environmental factors and spray additives (4). The environmental factor most important in the Midwest is moisture stress which can greatly modify plant growth and reduce the effectiveness of some POST herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental factor most important in the Midwest is moisture stress which can greatly modify plant growth and reduce the effectiveness of some POST herbicides. Environmental conditions such as relative humidity, temperature,and irradiance also have been found to affect bentazon activity (4). Retzlaff (8) suggested that, with higher temperatures, more bentazon penetrates into the plant than at lower temperatures in response to changes in the permeability of the plant cuticle and cell membranes.…”
Section: Introductionmentioning
confidence: 99%